Synthesis and protective effect of pyrazole conjugated imidazo[1,2-a]pyrazine derivatives against acute lung injury in sepsis rats via attenuation of NF-κB, oxidative stress, and apoptosis - Zang Binbin; Wang Lihui (Acta Pharmaceutica)
The current work was conducted to elucidate the pharmacological effect of pyrazole-conjugated imidazo[1,2-a]pyrazine derivatives against acute lung injury in rats in sepsis and their mechanism of action. Various pyrazole-conjugated imidazo[1,2-a]-pyrazine derivatives have been synthesized in a straightforward synthetic route. They exhibited a diverse range of inhibitory activity against NF-ĸB with IC50 ranging from 1 to 94 µmol L–1. Among them, compound 3h [(4-(4-((4-hydroxyphenyl)sulfonyl) phenyl)-5-(4-methoxyphenyl)-4,5-dihydro-1H-pyrazol-1-yl) (8-(methylamino)imidazo[1,2-a]pyrazin-2-yl)methanone] was identified as the most potent NF-κB inhibitor with IC50 of 1.02 µmol L–1. None of the synthesized compounds was found cytotoxic to normal cell-line MCF-12A. The pharmacological activity of the most potent NF-ĸB inhibitor 3h was also investigated in cecal ligation and puncture (CLP)-induced sepsis injury of the lung in rats. Compound 3h was administered to rats after induc tion of lung sepsis, and various biochemical parameters were measured. Results suggested that compound 3h significantly reduced lung inflammation and membrane permeability, as evidenced by H&E staining of lung tissues. It substantially reduced the generation of pro-inflammatory cytokines (TNF-α, IL-1B, IL-6) and oxidative stress (MPO, MDA, SOD). It showed attenuation of NF-ĸB and apoptosis in Western blot and annexin--PI assay, resp. Compound 3h also reduced the production of bronchoalveolar lavage fluid from the lung and provided a protective effect against lung injury. Our study showed the pharmacological significance of pyrazole-conjugated imidazo[1,2-a] pyrazine derivative 3h against acute lung injury in sepsis rats.